Fé na fronteira: colonização no oeste do Paraná e construção de uma hegemonia católica o caso de Quatro Pontes (PR) - Kinzler, Ademir Luis (2013)
enterprise Madeireira Colonizadora Rio Paraná S.A (known as Maripá) and the church, in the process of nationalization of the border, occupation and colonization in the current municipality of Quatro Pontes that had its beginning in the 1930 s , during the government of Getúlio Vargas, being that the occupation of the border areas in Brazil was named as "March to the West". There was a labor together between Maripá and the Catholic Church, as the church, appealing to Christian formation of Western man, helped to spread the paradisiacal features of the West of Paraná State. Such speech directly influenced the decision of immigrants in occupy empty demographic in this region, in this case, Quatro Pontes, moved by the speech of faith, hope and promise to obtain better living conditions. In other words, this means that such speech, used strategically, answered the interests of the Catholic Church to make its religion prevail, and the Colonization Maripá , profit from the sale of lands. The methodology of this study is based in bibliographic search, field research through interviews and the collection of oral sources, as well as the use of maps, pictures, registered books and tables